2009
DOI: 10.1186/1476-072x-8-42
|View full text |Cite
|
Sign up to set email alerts
|

An updated atlas of human helminth infections: the example of East Africa

Abstract: Background: Reliable and updated maps of helminth (worm) infection distributions are essential to target control strategies to those populations in greatest need. Although many surveys have been conducted in endemic countries, the data are rarely available in a form that is accessible to policy makers and the managers of public health programmes. This is especially true in sub-Saharan Africa, where empirical data are seldom in the public domain. In an attempt to address the paucity of geographical information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
159
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 46 publications
7
159
0
Order By: Relevance
“…9 A recent review of worm infection in East Africa reported median prevalence estimates in Nyanza Province of A. lumbricoides (18.5%), T. trichiura (11.9%), and hookworm (17.6%). 47 Third, there was considerable heterogeneity in delivery and uptake of the intervention. Only 25% of schools in the intervention reached the Government of Kenya standards for pupil/latrine ratios, only 25% had soap available for hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent review of worm infection in East Africa reported median prevalence estimates in Nyanza Province of A. lumbricoides (18.5%), T. trichiura (11.9%), and hookworm (17.6%). 47 Third, there was considerable heterogeneity in delivery and uptake of the intervention. Only 25% of schools in the intervention reached the Government of Kenya standards for pupil/latrine ratios, only 25% had soap available for hand washing.…”
Section: Discussionmentioning
confidence: 99%
“…Available data for Uganda indicate substantially higher rates of hookworm infestation in different settings (36,(60)(61)(62) . The atlas of human helminths in East Africa reports that at 6路5 %, the Central Region has the lowest prevalence of hookworm infestation in Uganda (19) . Ruralurban differences could account for the low prevalence we found as lower prevalence of hookworm infestation has been demonstrated in urban areas compared with rural areas (63)(64)(65) , although contradictory data have been reported from Zanzibar (66) .…”
Section: Discussionmentioning
confidence: 99%
“…This is due in part to the logistical advantages of school-based treatment, and in part to a perception of greater benefit connected with deworming in SAC. 8 The majority of research defining burden has also been performed in SAC, 9 however PSAC can also have considerable prevalence of STH infection 10,11 and experience morbidity. Furthermore, evidence does exist that PSAC benefit from deworming, [12][13][14] and others have advocated for their inclusion in MDA.…”
Section: Introductionmentioning
confidence: 99%
“…9,20,21 Plausible mechanisms are sanitation and hygiene conditions that favor STH transmission. 22,23 This susceptibility of slum areas, which house an estimated one-third of the world's population, 24 has been periodically recognized and addressed through deworming campaigns 21,25 and intervention trials 14,[26][27][28] ; however, there is no explicit guidance or consistent practice on distinguishing slums from other areas in agro-ecological zoning.…”
Section: Introductionmentioning
confidence: 99%